PENGEMBANGAN BENTUK PERMAINAN LOKOMOTOR, NON-LOKOMOTOR, DAN MANIPULATIF BERBASIS KETERAMPILAN DASAR BOLA VOLI DALAM PEMBELAJARAN PJOK KELAS 5 DI SDN KEBONSARI 2 KOTA MALANG - Febrianto, Rizky; Wiguno, Lokananta Teguh Hari (Inteligensi : Jurnal Ilmu Pendidikan, 2025)
This study aims to develop a form of locomotor, non-locomotor, and manipulative games based on basic volleyball skills that can be used in learning PJOK grade 5 at SDN Kebonsari 2 Malang City. this research utilizes the RD research and development model with steps adapted to the Borg Gall model. The test subjects consisted of class 5A students selected through cluster random sampling technique from a total of two existing classes, namely classes (5A and 5B). The development procedure includes needs analysis, research planning, initial product development, initial group test (small scale), revision of initial product trial results, main field test (large scale), data analysis and final revision. Data collection instruments in the form of needs analysis questionnaires aimed at students and teachers, validation of experts such as media experts, game experts, pjok learning experts, and also student response questionnaires. The results showed that the designed product is feasible to use in pjok learning in terms of media expert validation with the results of 98.1%, game experts at 91.6%, pjok learning experts at 97.1%, while based on the results of the small group test obtained a percentage value of 85.28% and a large group test of 89.13%. Thus, this game product is suitable for use as an alternative tool for learning pjok that is interesting and in accordance with the characteristics of grade 5 elementary school students.